The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1101/cshperspect.a031245
|View full text |Cite
|
Sign up to set email alerts
|

Osteoimmunology

Abstract: Bone is a crucial element of the skeletal-locomotor system, but also functions as an immunological organ that harbors hematopoietic stem cells (HSCs) and immune progenitor cells. Additionally, the skeletal and immune systems share a number of regulatory molecules, including cytokines and signaling molecules. Osteoimmunology was created as an interdisciplinary field to explore the shared molecules and interactions between the skeletal and immune systems. In particular, the importance of an inseparable link betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 286 publications
1
74
0
1
Order By: Relevance
“…Binding of RANKL to RANK in the presence of Mac colony‐stimulating factor (MCSF) stimulates differentiation of the osteoclast precursors into a multinucleated cell that eventually becomes mature osteoclast . When OPG concentrations are high relative to RANKL expression, OPG competes with and prevents RANKL from binding to RANK, which is associated with net decrease in osteoclastogenesis . In PD, excessive bone resorption occurs either due to up‐regulation of RANKL or down‐regulation of OPG, leading to an overall increase in the RANKL/OPG ratio .…”
Section: Inflammatory Mediators In Pathogenic Periodontal Osteoimmunementioning
confidence: 99%
See 1 more Smart Citation
“…Binding of RANKL to RANK in the presence of Mac colony‐stimulating factor (MCSF) stimulates differentiation of the osteoclast precursors into a multinucleated cell that eventually becomes mature osteoclast . When OPG concentrations are high relative to RANKL expression, OPG competes with and prevents RANKL from binding to RANK, which is associated with net decrease in osteoclastogenesis . In PD, excessive bone resorption occurs either due to up‐regulation of RANKL or down‐regulation of OPG, leading to an overall increase in the RANKL/OPG ratio .…”
Section: Inflammatory Mediators In Pathogenic Periodontal Osteoimmunementioning
confidence: 99%
“…31 When OPG concentrations are high relative to RANKL expression, OPG competes with and prevents RANKL from binding to RANK, which is associated with net decrease in osteoclastogenesis. 35 In PD, excessive bone resorption occurs either due to up-regulation of RANKL or downregulation of OPG, leading to an overall increase in the RANKL/OPG ratio. 36,37 Using murine models of PD and genetic manipulation of the RANKL/OPG system, multiple studies found that this axis is a core element of PD, and that an increase in RANKL mRNA expression and protein production leads to high RANKL/OPG ratio and uncoupling of bone formation-resorption cycle through enhanced osteoclastogenesis and osteoclast survival.…”
Section: F I G U R E 1 Overview Of the Effector Cells In The Pathogenmentioning
confidence: 99%
“…Osteoimmunology is an evolving and emerging concept in bone‐immune crosstalk in health and disease. The functions and interactions of the ‘osteoimmune system’ are performed by both bone cells and immune cells in the bone marrow; both cell types grow and develop in the same micromilieu and share many cytokines and signalling pathways . However, imbalanced osteoimmune regulation is not the only factor affecting immune responses in skeletal homeostasis between osteoclasts and osteoblasts, but molecules secreted from osteoclasts, osteoblasts and osteocytes differentially regulate the immune system, leading to diseases that affect bone loss, such as rheumatoid arthritis, osteoporosis and periodontitis …”
Section: Introductionmentioning
confidence: 99%
“…The activity of RANKL is controlled by its decoy receptor osteoprotegerin (OPG) (11)(12)(13). The interaction of RANKL and OPG is essential for the control of osteoclastogenesis (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%